Characteristics of Yersinia pseudotuberculosis isolated from animals in Brazil - Martins, C. H. [UNESP]; Bauab, T. M.; Falcão, D. P. (Journal Of Applied Microbiology, 1998)
Strains (105) of Yersinia pseudotuberculosis isolated in Brazil between 1982 and 1990 were bio-serotyped. They were also studied for plasmid profile, autoagglutination and calcium dependence at 37 degrees C, Congo red uptake, pyrazinamidase activity, esculin hydrolysis, salicin fermentation and drug sensitivity: 95.24% were biotype 2, serogroup O:3; 2.86% were biotype 1, serogroup O:1; and 1.90% were biotype 2, non-agglutinable. Plasmids were found in 77.14% of the strains (one in each strain). There was total correlation between the presence of the virulence plasmid and autoagglutination, calcium dependence at 37 degrees C and Congo red uptake. The esculin, salicin and pyrazinamidase tests were not efficient in differentiating pathogenic from non-pathogenic Y. pseudotuberculosis isolates. All strains were highly sensitive to the drugs used. These results indicate that Y. pseudotuberculosis is a potential pathogen for humans in Brazil, especially because the bio-serogroups detected among animals are those most frequently associated with human diseases.